Next day subjective and objective recovery indices following acute low and high training loads in academy Rugby Union players - Noon, M. R.; James, R. S.; Clarke, N. D.; Taylor, R. J.; Thake, C. D. (Sports, 2018)
The aim of this study was to determine the sensitivity of selected subjective and objective monitoring assessments in detecting changes in group and individual responses to low and high load bouts of high intensity intermittent exercise. In a counterbalanced crossover design, Thirteen Academy Rugby Union players (mean ± SD: age: 18 ± 1 years) performed a low load (15 min) and a high load (90 min) bout of high intensity intermittent exercise (Loughborough Intermittent Shuttle Test) one week apart. Monitoring assessments were performed immediately prior to and 20 h following each trial. Subjective self-report Well-being Questionnaire (WQ) items showed small to large deteriorations following the high load compared to low load (d = 0.4-1.5, p = 0.03-0.57). A very large increase in resting HR (HRrest) (d = 2.1, p = 0.02), moderate decrease in heart rate variability (HRV) indices (d = 0.7, p = 0.04 and d = 0.7, p = 0.01 for the natural logarithm of the standard deviation of R-R intervals (ln SDNN) and the root square of the mean squared differences of successive R-R intervals (rMSSD), respectively) and no change in countermovement jump (d = 0.0, p = 0.97) were evident following the high load compared to low load. Individual WQ responses revealed 7/9, 7/9, 6/9, 6/9, 5/9, 3/9 and 1/9 participants reported deteriorations in recovery, sleep quality, motivation, muscle soreness, fatigue, stress and appetite, respectively, following the high load compared to low load. Individual analysis indicated a negative response following the high load compared to low load in HRrest, ln SDNN and ln rMSSD for 4/6, 2/6 and 1/6 participants, respectively. Selected WQ items detected group and individual responses to high load and low load highlighting their potential utility. However, objective assessments lacked the sensitivity to detect small individual changes.